Science in the System of Spiritual Culture - Černienė, Bronislava (Problemos, 1984)
From the point of view of dialectic methodology every historic stage of the development of science is determined by the mode of production and by the forms of subjectivity present in culture. Marx’s idea of the science of future civilization as a unifying science about man serves as the criterion for the evaluation of modern scientific forms. Man is a universal being and he interacts with the world in many ways. Scientific knowledge is but one form of this interaction. The programme of development of all essential human powers presupposes development and organic interaction of all the forms of culture.